Sosiologi Pedesaan di Era Corona Virus 19 - Johan Wahyudi Adiluhung (Universitas Islam Darul Ulum Lamongan, 2020)
Rural sociology is one branch of sociology itself. Historically, it developed after the humanitarian aspects of agriculture gained attention in the United States, namely in 1908. The study began with the writings of a Christian priest who was in the socio-economic conditions of rural communities in northern America. Through this article, they solved the problems that arose in rural areas as a result of the birth of industry, which caused some rural areas to be abandoned. In addition, the end of the exploration of new areas to the West end of the 19th century. In the 1920s, courses on the subject of rural life began to be studied at various universities, especially at The American Sociological Society.